How does maternal pension wealth affect family old-age savings in Germany? - Andreas Thiemann (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper examines how families adjust their private old-age savings in response to a change in individual pension wealth. The regression discontinuity approach exploits two expansions of the child care pension benefit, in 1992 and in 1999, as natural experiments. The empirical analysis is based on three waves of the Survey of Income and Expenditure (EVS): 1998, 2003 and 2008. All results indicate that families do not adjust their private old-age savings in response to the increase in their pension wealth. From a political point of view, this suggests that the increase in individual pension wealth does not crowd-out old-age private savings. Hence, child care pension benefits increase a mother's old-age income without causing negative savings effects.
Keywords: D14; E21; H55; 330; old-age savings; pension wealth; regression discontinuity design